Super Turbo meets the cat-nappers - Powers, Edgar J. (Powers, Edgar J. Super Turbo graphic novels, 2022)
Super Turbo is excited to learn that he is going home with a student over the long holiday weekend, but his delight disappears when he encounters Meredith's two cats.